2000
DOI: 10.1542/peds.105.5.1029
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Evaluation of a Comprehensive Intervention Program for Asthmatic Children Enrolled in Medicaid

Abstract: A comprehensive asthma intervention program for Medicaid-insured asthmatic children can significantly improve health outcomes while reducing health care costs.asthma education, health care outcomes, Medicaid, asthma outreach, utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(129 citation statements)
references
References 31 publications
(13 reference statements)
5
119
1
4
Order By: Relevance
“…Additional long term studies are needed to confirm the findings of this cost analysis of nurseled outpatient management in patients with more severe asthma. Previous studies have evaluated the effect of educational intervention by asthma nurses on the costs of management of asthma both in children and adults [10,12,[22][23][24][25]. The economical consequences of these interventions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional long term studies are needed to confirm the findings of this cost analysis of nurseled outpatient management in patients with more severe asthma. Previous studies have evaluated the effect of educational intervention by asthma nurses on the costs of management of asthma both in children and adults [10,12,[22][23][24][25]. The economical consequences of these interventions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The economical consequences of these interventions were inconclusive. Some of these studies reported a cost reduction [10,12,22,23], whilst others found that extra investments were needed to achieve a reduction in healthcare utilisation of the patients [24,25]. In these studies, however, the asthma nurse intervention was additional to the routine medical care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric asthma outreach programs improve health outcomes and decrease costs, 67 as do intensive case management programs for children with diabetes. 68 In children with hypoplastic left heart syndrome, Ghanayem et al 69 reported improved survival between the first 2-staged surgical procedures with the use of an intensive home monitoring program.…”
Section: Comprehensive Heart Failure Programsmentioning
confidence: 99%